Exploring the Relationship between Foreign Language Classroom Anxiety and Speaking Performance among Students in EFL Setting - Eva Meidi Kulsum; Revi Nur Ridwan (Mathematics Education Study Program, 2025)
Speaking in a foreign language can cause anxiety for many EFL students and it can result a big impact on their performances and overall learning experiences. This study aims to explore the level of Foreign Language Classroom Anxiety (FLCA) and the relationship between FLCA and speaking performance among EFL students. This research employed a mix method research design, it is combination between descriptive qualitative and quantitative to explore the level of Foreign Language Classroom Anxiety (FLCA) and its correlation with students’ speaking performance. This research was conducted in one of universities in Bandung. 24 students who are English students were selected using purposive sampling techniques as participants of this study. Additionally, the findings imply that educators and institutions must prioritize strategies to reduce anxiety in speaking classes and highlight the need for awareness among teachers regarding the impact of anxiety on student performance. It is expected that teacher can create a supportive and non-judgmental environment in the classroom, reduce the pressure on individual students, and allow them to practice speaking in a less intimidating context.